DENGUE INCIDENCE IN BANDEIRANTES - PR, 2010 (Fiep Bulletin - online, 2012)
The dengue is one of the most important tropical illnesses of the present time, where the environment, the precariousness of basic sanitation and the lack of the public politics to control the endemics, contribute for the increase of the illness in the last decades.  The objective of this work was to verify the incidence of dengue notified cases in the town of Bandeirantes – PR, from January to July of 2010.  For information gathering it was utilized the Individual Investigation Inquiry (III) and the Individual Notification Inquiry (INI). In the period of study there were 639 cases notified with incidence of 193,7/10.000 inhabitants, out of which 58% were female sex, in all age groups.  Between the professions, 35.6% were students, housewives, pensioners and maids.  The cases notified were distributed almost through the town, however most of the cases were at the IBC Neighborhood (147 cases - 23.0% of the total of notifications).  The higher incidence occurred between the months of March and May.  The average temperature was 22,8°C and the average precipitation level was of 107.4 mm, favorable climatic conditions to the occurrence of dengue. 84.2% of the cases were positive and only 15.8% discarded.  The search of the patient for the health care service occurred in a short period of time; in 48% of the cases it occurred immediately after the appearance of the symptoms of the illness (less than seven days).  To ponder the peculiarities of the incidence of dengue is prominent to direct appropriate measures to the control the illness, improving the level of health of the population.
Keywords: dengue; incidence; notifications